Hyperbaric oxygen therapy as an adjunctive treatment for pyoderma gangrenosum: a case report - Katz, Alan A.; Thomson, Kristin; Amin, Ursa (International Journal of Research in Dermatology, 2021)
Pyoderma gangrenosum is an uncommon inflammatory dermatosis associated with chronic wounds. Diagnosis and management can be challenging to clinicians due to the relapsing nature of the disorder, atypical presentations, and exclusion of other conditions before diagnosis. Hyperbaric oxygen therapy is not a mainstay of treatment for pyoderma gangrenosum, but it is used for non-healing wounds associated with diabetes and vascular insufficiency due to its primary mechanism of tissue hyperoxia, resultant angiogenesis, and reduction of edema and inflammation. This case report presents two patients with pyoderma gangrenosum who were provided adjunctive therapy with hyperbaric oxygen with favorable outcomes.